2016
DOI: 10.1016/j.bioelechem.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high voltage nanosecond electric pulses on eukaryotic cells (in vitro): A systematic review

Abstract: For this systematic review, 203 published reports on effects of electroporation using nanosecond high-voltage electric pulses (nsEP) on eukaryotic cells (human, animal, plant) in vitro were analyzed. A field synopsis summarizes current published data in the field with respect to publication year, cell types, exposure configuration, and pulse duration. Published data were analyzed for effects observed in eight main target areas (plasma membrane, intracellular, apoptosis, calcium level and distribution, survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(91 citation statements)
references
References 87 publications
2
89
0
Order By: Relevance
“…First, this study utilized bulk electroporation to deliver plasmids into the human NP cells and there can be limitations associated with this technique namely high voltage pulses to allow plasmids to permeate through the lipid bilayer . Outcomes include potential apoptosis, necrosis or cellular dysfunction (possibly senescence) . Our results demonstrated high cell viability up to 4 weeks and cellular morphology characteristic of the cell type.…”
Section: Ecm Synthesis and Degradationmentioning
confidence: 94%
“…First, this study utilized bulk electroporation to deliver plasmids into the human NP cells and there can be limitations associated with this technique namely high voltage pulses to allow plasmids to permeate through the lipid bilayer . Outcomes include potential apoptosis, necrosis or cellular dysfunction (possibly senescence) . Our results demonstrated high cell viability up to 4 weeks and cellular morphology characteristic of the cell type.…”
Section: Ecm Synthesis and Degradationmentioning
confidence: 94%
“…Only 44% reported a formal risk of bias assessment (Cochrane, GRADE, SYRCLE, Tool for Studies with Diverse Designs), one reported their own grading system [56]. Of the four reviews reporting Cochrane or SYRCLE tools it was notable that the majority of domains were rated as unclear, reiterating that the study designs are not based on randomisation, allocation concealment or blinding [5760]. This finding agrees with our own assessments and indicates that basic research requires its own risk of bias tools.…”
Section: Resultsmentioning
confidence: 99%
“…75% reviews did not consider how valid the markers were. One review did consider the marker validity [66], three discussed outcome validity or quantification methods [57,62,63]. 69% of reviews did not consider the impact of imprecision; those that did consider any aspect of imprecision reported minimal details.…”
Section: Resultsmentioning
confidence: 99%
“…Retelj et al, 2013; PAULY and SCHWAN, 1959; Sundararajan, 2008). Moreover, it was also hypothesized that pulse frequencies above 100 kHz allow the applied electric field to reach the intracellular structures (Batista Napotnik et al, 2016; Gowrishankar and Weaver, 2003; Schoenbach et al, 2001). Thus, it was believed that electric pulse trains that have nano-second pulse widths and frequencies above 100 kHz allow electric perturbation of voltage sensitive intracellular processes of the endoplasmic reticulum, mitochondria, and the nucleus (Chopinet et al, 2013; Schoenbach et al, 2004).…”
Section: Discussionmentioning
confidence: 99%